Query Expansion based on Local Distributional Thesauri - da Silva, Fabiano Tavares; Maia, José Everardo Bessa (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
This work proposes and evaluates an approach to query expansion in Information Retrieval based on Local Context Analysis using a Distributional Semantic Representation. In general, the approach performed better compared to that of query expansion using non-distributional, local or global techniques, running over datasets of different application domains.